Do parents expect too much or is it all about grades? The discrepancy between parents’ aspirations and child’s academic performance, and parental satisfaction with the school - Stefani Milovanska-Farrington (Cogent Economics & Finance)
Schooling is related to health and future labor market outcomes. The school parents choose for their children often depends on feedback received from other parents. Therefore, it is important to understand whether parental satisfaction with the school depends only on objective measures of the quality of the school. We examine the association between children’s academic performance, parents’ aspirations, the mismatch between the two, and parents’ satisfaction with different aspects of children’s schooling. The findings suggest that excellent academic performance of the child is associated with higher parental satisfaction, regardless of parents’ aspirations. High expectations accompanied by low performance are negatively related to parental satisfaction with all aspects of children’s schooling. The results have implications related to school rankings and the significance of parental school reviews.